Hazards of baby walkers in a European context. Issue 2 (June 1996) - Petridou, E.; Simou, E.; Skondras, C.; Pistevos, G.; Lagos, P.; Papoutsakis, G.
Abstract : OBJECTIVES: To identify conditions related to baby walker injuries in a Greek population. DESIGN: Analysis of all baby walker related injuries recorded during a 12 month period by the childhood injury surveillance system established in one of the two teaching hospitals for children serving the population of Athens. SETTING: Emergency clinics of A Kyriakou Children's Hospital in Athens, Greece. SUBJECTS: 49 babies with baby walker related injuries brought to the emergency clinics during the period May 1994 to April 1995. RESULTS: The incidence of these injuries was 16 per thousand person years of users, or 3.5 per thousand babies per year. More boys than girls were brought to the hospital for these injuries and the incidence density was highest during the ninth and 10th month of age. Falls from heights, particularly stairs, were the most frequent cause of baby walker related injuries, especially among younger babies. The majority of these injuries were of minor severity, but three babies had bone fractures and one had a second degree facial burn. Six babies required hospitalization and for seven others, a follow up visit was needed. The higher proportion of hospitalization among girls than boys raises the possibility that boys with minor injuries are more frequently brought to the hospital. CONCLUSIONS: Baby walkers impart a significant risk of injury from a consumer product that provides no clearly identifiable benefit. As most baby walker injuries happen on stairs, modifications in product design are required to reduce these injuries. Moreover, parents should be forcefully advised of the risks and predisposing conditions, if baby walkers are to be used at all.